Respuesta :
Answer:
[tex]y-3=\frac{3}{4} (x-5)\\\\y-3=\frac{3}{4}x-\frac{3}{4}(5)\\\\y=\frac{3}{4} x+3-\frac{15}{4} \\\\y=\frac{3}{4} x+\frac{12}{4} -\frac{15}{4} \\\\y=\frac{3}{4} x-\frac{3}{4}[/tex]
Is this standard form? :\
Answer:
3x-4y=3
Step-by-step explanation:
Hi there!
We are given the equation y-3=[tex]\frac{3}{4}(x-5)[/tex], and we want to write it in standard form
Standard form is given as ax+by=c, where a, b, and c are integer coefficients, a CANNOT be 0 and CANNOT be negative, and b also CANNOT be 0
So let's expand the parentheses in the equation
Do the distributive property
y-3=[tex]\frac{3}{4}x-\frac{15}{4}[/tex]
Add 3 to both sides
y=[tex]\frac{3}{4}x-\frac{3}{4}[/tex]
We expanded the parentheses, but the equation is now in slope-intercept form (y=mx+b, where m is the slope and b is the y intercept)
Remember that we want it in standard form, which is ax+by=c
Subtract [tex]\frac{3}{4}x[/tex] from both sides
[tex]\frac{-3}{4}x+y=\frac{-3}{4}[/tex]
Remember that the coefficients of a, b, and c need to be integers, and also that a (the coefficient in front of x) CANNOT be negative
So multiply both sides by -4
[tex]-4(\frac{-3}{4}x+y)=-4(\frac{-3}{4})[/tex]
Distribute -4 to every number
[tex]-4(\frac{-3}{4}x)+-4(y)=-4(\frac{-3}{4})[/tex]
Multiply
[tex]\frac{12}{4}x-4y=\frac{12}{4}[/tex]
Simplify
3x-4y=3
There's the equation in standard form
Hope this helps!